2023
DOI: 10.3390/ma16041360
|View full text |Cite
|
Sign up to set email alerts
|

Development of Alkali-Activated Porous Concrete Composition from Slag Waste

Abstract: In this paper, a porous alkali-activated slag concrete was developed that can be used in the construction sector as a sustainable building material and potentially as an alternative to the aerated concrete products currently on the market. Ferrous slag from the metallurgical industry (Finland) and phosphogypsum from a fertilizer plant (Lithuania) were used as precursors in alkali-activated systems. The addition of hydrogen peroxide and phosphogypsum led to positive changes in the final properties of the test m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The production of PG-based lightweight concrete consumes 74 billion tons of waste per year, and if planted on these lands, it can indirectly release more than 90,000 tons of oxygen, which greatly improves the environment. To recycle PG for the production of porous concrete, ferrous slag, cement, hydrogen peroxide were added to prepare concrete [74]. The results of the study showed that hydrogen peroxide and PG had a positive effect on the performance of the system, while the strength of the concrete was up to 7.95 MPa and the density was as low as 830 kg/m 3 , and the final optimum admixture of PG was 5%.…”
Section: Other Materialsmentioning
confidence: 99%
“…The production of PG-based lightweight concrete consumes 74 billion tons of waste per year, and if planted on these lands, it can indirectly release more than 90,000 tons of oxygen, which greatly improves the environment. To recycle PG for the production of porous concrete, ferrous slag, cement, hydrogen peroxide were added to prepare concrete [74]. The results of the study showed that hydrogen peroxide and PG had a positive effect on the performance of the system, while the strength of the concrete was up to 7.95 MPa and the density was as low as 830 kg/m 3 , and the final optimum admixture of PG was 5%.…”
Section: Other Materialsmentioning
confidence: 99%
“…Furthermore, it explores the development trend of the strength and shrinkage characteristics of the aforementioned materials under the influence of waste slag ratio, cement dosage and time, and clarified the microstructure of the concrete by Scanning Electron Microscope (SEM). Then, it comprehensively investigated the formation mechanisms of strength and shrinkage performance, aiming at providing a reference for relieving the pressure of natural sand and gravel mining, consuming industrial solid waste, building a sustainable green economic system in China and promoting the early formation of social double carbon strategy [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%